2023
DOI: 10.3847/1538-4365/acdf5d
|View full text |Cite
|
Sign up to set email alerts
|

Linear Mode Decomposition in Magnetohydrodynamics Revisited

G. P. Zank,
L.-L. Zhao,
L. Adhikari
et al.

Abstract: Small-amplitude fluctuations in the magnetized solar wind are measured typically by a single spacecraft. In the magnetohydrodynamics (MHD) description, fluctuations are typically expressed in terms of the fundamental modes admitted by the system. An important question is how to resolve an observed set of fluctuations, typically plasma moments such as the density, velocity, pressure, and magnetic field fluctuations, into their constituent fundamental MHD modal components. Despite its importance in understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 70 publications
0
29
1
Order By: Relevance
“…We find that solar wind fluctuations in the young solar wind, i.e., near the Sun, are predominantly 2D and not slab, consistent with previous findings from theoretical and observational studies (Zank & Matthaeus 1992b, 1993Bieber et al 1996;Zank et al 2017;Adhikari et al 2022). This conclusion is contrary to the prior results of Bandyopadhyay & McComas (2021) and Zhao et al (2022), indicating that a closer analysis is warranted, possibly using the mode-decomposition analysis developed recently by Zank et al (2023), which is distinct from both these analyses and that presented here. An intriguing prospect is to extend this analysis from the sub-Alfvénic region to the super-Alfvénic region, including distances up to 1 au.…”
Section: Discussioncontrasting
confidence: 99%
“…We find that solar wind fluctuations in the young solar wind, i.e., near the Sun, are predominantly 2D and not slab, consistent with previous findings from theoretical and observational studies (Zank & Matthaeus 1992b, 1993Bieber et al 1996;Zank et al 2017;Adhikari et al 2022). This conclusion is contrary to the prior results of Bandyopadhyay & McComas (2021) and Zhao et al (2022), indicating that a closer analysis is warranted, possibly using the mode-decomposition analysis developed recently by Zank et al (2023), which is distinct from both these analyses and that presented here. An intriguing prospect is to extend this analysis from the sub-Alfvénic region to the super-Alfvénic region, including distances up to 1 au.…”
Section: Discussioncontrasting
confidence: 99%
“…Observationally, the presence of quasi-2D turbulence is demonstrated by the "Maltese-cross"-like structure of the correlation function (Matthaeus et al 1990;Dasso et al 2005), by the anisotropic turbulence measurements (Bandyopadhyay & McComas 2021;Zhao et al 2022a), and its consistency with cosmic-ray mean free paths (Bieber et al 1994;Zhao et al 2017). Multi-SC observations also provide evidence of low-frequency fluctuations (Sahraoui et al 2010) and nonpropagating modes (Zank et al 2023;Zhao et al 2023) in the solar wind.…”
Section: Introductionmentioning
confidence: 88%
“…In a similar vein, one would like to distinguish between density fluctuations (e.g., Kontar et al 2023) generated by compressible fast and slow magnetosonic (MS) waves and advected density fluctuations (entropy modes). Zank et al (2023) revisited and developed a very general mode decomposition method that identifies wave modes and advected structures, such as magnetic islands or entropy modes, while evaluating the corresponding phase information. By utilizing the newly developed mode decomposition technique, we reanalyze the first sub-Alfvénic solar wind interval observed by PSP.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that a classical mode decomposition analysis (Glassmeier et al 1995) was applied to various plasma intervals observed during the first PSP encounter by Chaston et al (2020) and Zhao et al (2021b). Unlike the method introduced by Zank et al (2023), the classical method projects the observed fluctuations onto a subspace of possible MHD modes comprising only three possible modes, the planar Alfvén, and fast and slow MS modes, and all three modes share the same wavevector (Zhao et al 2021b). The classical approach does not include advected modes (entropy modes, magnetic islands, Alfvén vortices) nor the full spherical Alfvén mode, all of which are incorporated in the analysis presented in Zank et al (2023), together with the fast and slow MS modes.…”
Section: Introductionmentioning
confidence: 99%